Education in debate: new looks for the formation of the subject - Vargas, Thaís Conte; Cruz, José Anderson Santos; Bizelli, José Luis (Revista Hipótese, 2018)
Thinking about education involves many challenges that are linked to the development of teaching and learning methods, teacher training, school management forms and institutional designs of educational policies. However, we want to draw attention to the issue regarding the training of students to build their autonomy. The formal education must interact with the student’s life as a citizen, with cultural knowledge acquired outside of the School, in the construction of the polis and, currently, in the life within the digital network. The conservative formulas of facing the exercise of classroom as a filling for empty structures of contents taught in boxes of disciplines by a specialist teacher come up short of the expected. An inflexible curriculum of disciplines reflects a reality that hardly leads to education, to the conscious exercise of the freedom of reflection, to criticize and create collectively, and to solve problems of the everyday life. Autonomy practiced by citizens who divide the classroom as an adventure of knowledge incorporates culture in the pedagogical didactic action, that requires a laboratory that goes beyond the walls of the School, gaining space in concrete society. This is the object of our analysis.